1995
DOI: 10.1007/bf01700975
|View full text |Cite
|
Sign up to set email alerts
|

Primary laryngospasm in a patient with Parkinson's disease: Treatment with CPAP via minitracheostomy following intubation

Abstract: Building on data published by M C Vos and colleagues in 1992 on imipenem/cilastatin and CAVHD [1] we in vestigated imipenem/cilastatin in 16 pa tients with (n = 10, group 1) and without in = 6, group 2) renal insufficiency; both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Although many of these patients had normal vocal cord studies when awake, virtually all demonstrated paradoxical cord movements, or even paralysis, when sleep was induced with benzodiazepines. EMG studies have illustrated that it is dystonia, not paralysis which causes the stridor in these cases 3. Such diurnal variation parallels that seen in our case of Parkinson’s disease, with normal vocal cord movement early in the day and paradoxical movements becoming apparent in the late evening.…”
Section: Commentsupporting
confidence: 81%
See 2 more Smart Citations
“…Although many of these patients had normal vocal cord studies when awake, virtually all demonstrated paradoxical cord movements, or even paralysis, when sleep was induced with benzodiazepines. EMG studies have illustrated that it is dystonia, not paralysis which causes the stridor in these cases 3. Such diurnal variation parallels that seen in our case of Parkinson’s disease, with normal vocal cord movement early in the day and paradoxical movements becoming apparent in the late evening.…”
Section: Commentsupporting
confidence: 81%
“…Although stridor and severe respiratory compromise are well-recognised complications of another synucleinopathy, multiple system atrophy,1, 2 it has seldom been reported in idiopathic Parkinson’s disease 35. By contrast, in multiple system atrophy, both focal laryngeal dystonia and vocal cord paresis have been implicated in the development of stridor 6, 7.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the ninety-five published studies, six [46–51] report the use in patients with acute upper airway obstructions, one [19] describes the use in two patients with upper airway obstructions (it did not specify if it was for an acute process), and none describes the use of mini tracheostomies for obstructive sleep apnea; see Figure 1. The MTK tracheostomy tubes are small-bore cannulas and have an internal diameter of 4 mm, an outer diameter of 5.4 mm, and a length of 90 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Primary laryngospasm is a known complication of PD and acute withdrawal of treatment can cause airway obstruction. 13 Dentition is often impaired. Patients who have been receiving dilantin may have gum hypertrophy and loosening of teeth that may hamper placement of an airway.…”
Section: Preanesthetic Assessmentmentioning
confidence: 99%